Amulet or Watchman Device for Percutaneous Left Atrial Appendage Closure: Primary Results of the SWISS-APERO Randomized Clinical Trial. Issue 10 (8th March 2022) - Galea, Roberto; De Marco, Federico; Meneveau, Nicolas; Aminian, Adel; Anselme, Frédéric; Gräni, Christoph; Huber, Adrian T.; Teiger, Emmanuel; Iriart, Xavier; Babongo Bosombo, Flora; Heg, Dik; Franzone, Anna; et al.
Abstract : Background: No study has so far compared Amulet with the new Watchman FLX in terms of residual left atrial appendage (LAA) patency or clinical outcomes in patients undergoing percutaneous LAA closure. Methods: In the investigator-initiated SWISS APERO trial (Comparison of Amulet Versus Watchman/FLX Device in Patients Undergoing Left Atrial Appendage Closure), patients undergoing LAA closure were randomly assigned (1:1) open label to receive Amulet or Watchman 2.5 or FLX (Watchman) across 8 European centers. The primary end point was the composite of justified crossover to a nonrandomized device during LAA closure procedure or residual LAA patency detected by cardiac computed tomography angiography (CCTA) at 45 days. The secondary end points included procedural complications, device-related thrombus, peridevice leak at transesophageal echocardiography, and clinical outcomes at 45 days. Results: Between June 2018 and May 2021, 221 patients were randomly assigned to Amulet (111 [50.2%]) or Watchman (110 [49.8%]), of whom 25 (22.7%) patients included before October 2019 received Watchman 2.5, and 85 (77.3%) patients received Watchman FLX. The primary end point was assessable in 205 (92.8%) patients and occurred in 71 (67.6%) patients receiving Amulet and 70 (70.0%) patients receiving Watchman, respectively (risk ratio, 0.97 [95% CI, 0.80–1.16]; P =0.713). A single justified crossover occurred in a patient with Amulet who fulfilled LAA patency criteria at 45-day CCTA. Major procedure-related complications occurred more frequently in the Amulet group (9.0% versus 2.7%; P =0.047) because of more frequent bleeding (7.2% versus 1.8%). At 45 days, the peridevice leak rate at transesophageal echocardiography was higher with Watchman than with Amulet (27.5% versus 13.7%, P =0.020), albeit none was major (ie, >5 mm), whereas device-related thrombus was detected in 1 (0.9%) patient with Amulet and 3 (3.0%) patients with Watchman at CCTA and in 2 (2.1%) and 5 (5.5%) patients at transesophageal echocardiography, respectively. Clinical outcomes at 45 days did not differ between the groups. Conclusions: Amulet was not associated with a lower rate of the composite of crossover or residual LAA patency compared with Watchman at 45-day CCTA. Amulet, however, was associated with lower peridevice leak rates at transesophageal echocardiography, higher procedural complications, and similar clinical outcomes at 45 days compared with Watchman. The clinical relevance of CCTA-detected LAA patency requires further investigation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03399851. Abstract : Supplemental Digital Content is available in the text.